The Influence of Learning Style and Interest on Students' Cognitive Ability in Entrepreneurship Courses - Sharfina Amima; Muhammad Rahmattullah; Lasiani (Journal of Educational Management Research, 2026)
This study aims to analyze the partial influence of Learning Styles (Visual, Auditory, Kinesthetic/VAK) and Learning Interest on students' cognitive abilities in Entrepreneurship courses, focusing on the Wetland Entrepreneurship context at FKIP ULM. The primary objective is to identify how these factors impact students' higher-order cognitive skills (analysis, evaluation, creation), particularly given the high failure rate (78.5% failed pre-test). This quantitative study employs an explanatory correlation design with a case study approach, involving 94 students from the Wetland Entrepreneurship course at FKIP ULM, selected via purposive sampling. Data were gathered through questionnaires (Learning Styles and Interest) and cognitive tests/course scores (Cognitive Ability). Analysis was conducted using One-Way ANOVA for Learning Styles and Simple Regression (t-test) for Learning Interest. The results indicate no significant difference in cognitive abilities across VAK learning style groups (Sig. 0.503 > 0.05). However, Learning Interest emerged as a significant partial predictor of cognitive ability (Sig. 0.000 < 0.05), explaining 51.8% of the variance (R² = 0.518). The study's implication is that enhancing students' cognitive performance should focus on strategies that foster Learning Interest, rather than prioritizing VAK learning style preferences, which were found to be insignificant in predicting cognitive outcomes. Future research should explore context-based learning models that increase student engagement within the wetland environment.